Oral lichen planus: An overview - R Jayasri Krupaa; S Leena Sankari; K. M. K. Masthan; E Rajesh (Wolters Kluwer Medknow Publications, 2015)
Lichen planus is an immunologically mediated mucocutaneous disease that is triggered by varied etiological agents. The oral lichenoid reaction is considered a variant of the disease that needs to be clearly diagnosed as a separate entity from oral lichen planus and treated. They follow a strict cause-effector relationship, protocols that suggest the differentiation. Lichen planus has varied clinical forms in the oral mucosa and cutaneously that has different prognosis. This condition also arises in association with various other systemic conditions such as hypertension, diabetes mellitus. There have been cases reported in the esophagus, larynx, scalp, nail, cutaneous areas, especially arms and wrists, trunk. There is reported malignant transformation that essentiates careful examination, treatment protocol and regular follow-up sessions. This article throws light on the disease condition of oral lichen planus and oral lichenoid reaction that is essential for the differentiation and treatment.